RETHINKING LOCAL KNOWLEDGE: DIGITIZING LOCAL KNOWLEDGE BETWEEN EXTINCTION AND SUSTAINABILITY - Halim, Paisal; Badruddin, Syamsiah; P, Suci Ayu Kurniah (Universitas Nasional, 2025)
This study investigates the impact of digitalization on the preservation of local knowledge within the Ammatoa Kajang community in South Sulawesi. It specifically addresses the research questions: (1) What forms of local knowledge in the Ammatoa Kajang community are suitable for digitization? (2) What are the challenges and opportunities in digitizing local knowledge in this context? (3) How can participatory and ethical approaches ensure the preservation of local knowledge through digital technologies? Local knowledge, including value systems, customary law, and ecological rituals like Ma'bara, is increasingly at risk of extinction due to globalization and cultural commodification. Employing a qualitative ethnographic approach, the study reveals that digitalization can serve as an effective tool for expanding intergenerational knowledge, provided it is guided by participatory principles, community control, and strong cultural ethics. The findings suggest that without the active involvement of indigenous communities, digitalization may undermine the symbolic meaning and spirituality of this knowledge. The study also highlights key limitations, including the risk of decontextualization and cultural misrepresentation when digitalization is not community-driven. This research underscores the need for collaborative strategies, digital-based cultural protection policies, and approaches aligned with local values to safeguard traditional knowledge in the digital era.